Identification of limb-specific Lmx1b auto-regulatory modules with Nail-patella syndrome pathogenicity - Endika Haro (Nature Portfolio, 2021)
Nail-patella syndrome (NPS) is characterized by nail dysplasia, absent/hypoplastic patellae, chronic kidney disease, and glaucoma and can be caused by haploinsufficiency of LMX1B; however, not all patients harbor pathogenic LMX1B mutations. Here the authors show that loss-of-function variations in upstream enhancer sequences are responsible for a limb specific form of human NPS.